2019
DOI: 10.1111/pace.13779
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde His bundle activation during right ventricular overdrive pacing in supraventricular tachycardia

Abstract: Background Differentiation between atrioventricular nodal re‐entrant tachycardia (AVNRT), atrioventricular re‐entrant tachycardia (AVRT), and atrial tachycardia (AT) is often challenging during electrophysiology studies. This study compared the sensitivity and specificity of identifying anterograde His bundle activation during entrainment with commonly used right ventricular (RV) pacing maneuvers to differentiate between these types of supraventricular tachycardia (SVT). Methods Out of 112 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The atria and ventricles play important roles in atrioventricular node re-entry tachycardia and atrioventricular re-entry tachycardia[ 12 ]. The ECG of our patient showed that the atria and ventricles were separated, which excluded supra VT.…”
Section: Discussionmentioning
confidence: 99%
“…The atria and ventricles play important roles in atrioventricular node re-entry tachycardia and atrioventricular re-entry tachycardia[ 12 ]. The ECG of our patient showed that the atria and ventricles were separated, which excluded supra VT.…”
Section: Discussionmentioning
confidence: 99%
“…We read the article "Anterograde His bundle activation during right ventricular overdrive pacing in supraventricular tachycardia" by Elbatran et al with interest. 1 We believe that their study is likely pacing. [2][3][4] These maneuvers are useful for the differential diagnosis of AVNRT, AVRT, and AT.…”
Section: Dear Editormentioning
confidence: 96%
“…We read the article “Anterograde His bundle activation during right ventricular overdrive pacing in supraventricular tachycardia” by Elbatran et al with interest . We believe that their study is likely to form a valuable addition to the literature.…”
mentioning
confidence: 96%
“…The comments by Ozcan Celebi et al are insightful and raise the question of how to improve the detection of anterograde His bundle activation. Anterograde His bundle activation is an intracardiac manifestion of fusion . As a result, it can be easier to demonstrate when fusion occurs more distally within the ventricle below the level of the His bundle.…”
mentioning
confidence: 99%
“…Placing closely spaced multielectrode catheters at the His position can enhance the yield of this manoeuvre, first by providing multiple His bundle recordings from which to assess anterograde His activation and second by suggesting the direction of activation of the His bundle and right bundle branch (proximal to distal with anterograde activation) and comparing it to activation during tachycardia.…”
mentioning
confidence: 99%